Key Technology of Agricultural Production and Market Information Matching in Big Data Era - Shuo Wang; Shihong Liu (Institute of Advanced Engineering and Science, 2014)
This article describes challenges faced by agricultural production and marketing in the era of big data, and then builds the agricultural market information matching platform based on HADOOP & NUTCH combining cloud computing technology, finally details its layers and key technologies, including the use of open source search engine to capture the whole network market information to build agricultural production and market data sources, users’ interest model and the combination of matching algorithm and HADOOP environment. The aim of this paper is to make the agricultural market information matching platform more suitable for Chinese agricultural production and marketing system in order to solve the bottleneck problems such as information overload, lack of storage space, scalability and efficiency of analysis and calculation. As a result, this thesis provides a useful reference and new strategy for analysis and mining of big data in agricultural production and marketing areas. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4489